Maple in mathematics education and research : Third Maple Conference, MC 2019, Waterloo, Ontario, Canada, October 15-17, 2019, Proceedings /: Third Maple Conference, MC 2019, Waterloo, Ontario, Canada, October 15-17, 2019, Proceedings. (2020) - Unknown
No abstract available